When it pays off to take a look: Infants learn to follow an object's motion with their gaze—Especially if it features eyes. (9th March 2022) - Michel, Christine; Pauen, Sabina; Hoehl, Stefanie
Abstract: Social cues and instrumental learning are two aspects potentially fostering early gaze following. We systematically investigated the influence of social features (schematic eyes vs. reverse‐contrast eyes) and gaze‐contingent reinforcement (elicited vs. not elicited) on 4‐month‐olds' learning to attend to gaze‐cued objects. In 4 experiments, we tested infants' ( N = 74) gaze following of a turning block with schematic or reverse‐contrast eyes. In Experiments 1 and 2, infants could elicit an attractive animation in a training phase via interactive eye tracking by following the turning of the block. Experiments 3 and 4 were yoked controls without contingent reinforcement. Infants did not spontaneously follow the motion of the block. Four‐month‐olds always followed the block after training when it featured schematic eyes. When the block featured reverse‐contrast eyes, the training phase only affected infants' looking behavior without reinforcement. While speaking to a certain degree of plasticity, findings stress the importance of eyes for guiding infants' attention.